2019
DOI: 10.1139/cjb-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

The photosynthetic apparatus ofConocarpus lancifoliusEngl. (Combretaceae) suffers damage in soil contaminated with heavy metals

Abstract: Conocarpus lancifolius Engl. (Combretaceae), a heat tolerant plant, has potential for use in the phytoremediation of polluted soil. We analyzed the physiological changes in C. lancifolius exposed to single and mixed heavy metals (HMs; cadmium, nickel, and lead). For 30 days under controlled growth conditions, we exposed some groups of plants to a single HM at concentrations of 25 or 50 μmol·L–1 and other groups were exposed to 25 μmol·L–1 of a mixture of HMs. Photosynthetic parameters such as electron transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In a study of six HMs in maize, the order of toxicity was established to be Cd > Co > Hg > Mn > Pb > Cr (Ghani 2010 ). We have previously reported the effect of HMs on the C. lancifolius photosynthetic apparatus (Redha et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study of six HMs in maize, the order of toxicity was established to be Cd > Co > Hg > Mn > Pb > Cr (Ghani 2010 ). We have previously reported the effect of HMs on the C. lancifolius photosynthetic apparatus (Redha et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher accumulation of highly toxic Pb and Cd shows that C. lancifolius preferentially accumulated these HMs. This is because C. lancifolius has a high growth rate with a large green crown (Redha et al 2019 ). Observations during this study revealed that C. lancifolius also has long hairy roots.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations